2007
DOI: 10.1152/ajpheart.01276.2006
|View full text |Cite
|
Sign up to set email alerts
|

Atrial myocardium is the predominant inotropic target of adrenomedullin in the human heart

Abstract: Adrenomedullin (ADM) is an endogenous peptide with favorable hemodynamic effects in vivo. In this study, we characterized the direct functional effects of ADM in isolated preparations from human atria and ventricles. In electrically stimulated human nonfailing right atrial trabeculae, ADM (0.0001-1 micromol/l) increased force of contraction in a concentration-dependent manner, with a maximal increase by 35 +/- 8% (at 1 micromol/l; P < 0.05). The positive inotropic effect was accompanied by a disproportionate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
4
9
0
Order By: Relevance
“…Admr, receptor of the potent vasodilator adrenomedullin, and its chaperone protein Ramp2 were both highly expressed in the right atrium, whereas the related CALCRL receptor, together with its chaperone protein Ramp1, were expressed throughout the heart. This result is consistent with data showing that adrenomedullin exerts Ca 2ϩ -dependent-positive inotropic effects in human atria and, to a lesser extent, in ventricular myocardium (Bisping et al, 2007). Only the chemokine Ccr10rr receptor and two orphan receptors, Pgr1 and GPR162, constituted the signature of the left atrium.…”
Section: Discussionsupporting
confidence: 92%
“…Admr, receptor of the potent vasodilator adrenomedullin, and its chaperone protein Ramp2 were both highly expressed in the right atrium, whereas the related CALCRL receptor, together with its chaperone protein Ramp1, were expressed throughout the heart. This result is consistent with data showing that adrenomedullin exerts Ca 2ϩ -dependent-positive inotropic effects in human atria and, to a lesser extent, in ventricular myocardium (Bisping et al, 2007). Only the chemokine Ccr10rr receptor and two orphan receptors, Pgr1 and GPR162, constituted the signature of the left atrium.…”
Section: Discussionsupporting
confidence: 92%
“…AM is a vasorelaxant peptide with favorable hemodynamic effects in vivo. Prior studies suggest that AM exerts potent inotropic effect in the atria as well as in the ventricle (2,45). We found that atrial stretch led to a significant decrease in both AM and AM receptor mRNA levels, suggesting a substantial downregulation of local AM system.…”
Section: Discussionsupporting
confidence: 51%
“…However, the response of atrial myocardium to various agents could be different from that of the ventricular myocardium. Endothelin [16], calcitonin gene-related peptide [17], and adrenomedulin (ADM) [18] all show pronounced inotropic effects on the atrial myocardium but smaller or even no (angiotensin II) effect on the ventricular myocardium. Flagg et al [19] found a previously unidentified K ATP channel heterogeneity: SUR1 is an essential component of the K ATP channels in atrial but not ventricular cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%